Manohara Case Analysis to Understand Agenda Setting Theory - Rudiman Rudiman; Arfan Suryadi; Faisyal Andriansyah (Trigin Publisher, 2020)
The circulation of news of Domestic Violence (KDRT) experienced by Manohara Odelia Pinot spread in various news media both print and digital in 2009, everyone in cyberspace discussed the news. Even the news related to his case was able to match the election news at that time. Although this issue should not be discussed too much, in fact almost all Indonesian people know about this case. This has spread due to the role of the mass media, both print, electronic and online media, which continuously preach the news. The media are blowing up news about the case experienced by Manohara. This study aims to explain how we understand how the media work to direct public attention, to government policies and make it easier to understand Agenda Setting Theory. Because this phenomenon is an illustration of how strong the influence of the mass media in the formation of public opinion. The mass media have the ability to select and emphasize certain topics that they consider important (setting the 'agenda'/media agenda) which in this case is related to the Agenda Setting theory. Where in the Agenda Setting theory there are three agenda setting processes, namely the media agenda, public agenda, and policy agenda.